Arthur lost and found - Brown, Marc Tolon (Boston : Little, Brown, 1998)
When Arthur and Buster try to take the bus to Arthur's swimming lesson, they fall asleep and end up in a strange part of town.
370
Accelerated Reader AR
Keywords: Aardvark -- Juvenile fiction; Buses -- Juvenile fiction; Missing children -- Juvenile fiction